Management of symptomatic sacral perineural cysts. - Jianqiang Xu (Public Library of Science (PLoS), 2012)
Background There has been no consensus on the optimal treatment of symptomatic sacral perineural cysts. Most previous reports concerning the management methods were either sporadic case reports or a series of limited cases. This study is to further optimize the management for patients with symptomatic sacral perineural cysts by analyzing the outcomes of a cohort of patients who were treated with different strategies. Methods and findings We reviewed the outcomes of 15 patients with symptomatic sacral perineural cysts who were managed by three different modalities from 1998 through 2010. Six patients underwent microsurgical cyst fenestration and cyst wall imbrication. Seven patients underwent a modified surgical procedure, during which the cerebrospinal fluid leak aperture was located and repaired. Two patients were treated with medication and physical therapy. Outcomes of the patients were assessed by following up (13 months to 10 years). All of the six patients treated with microsurgical cyst fenestration and cyst wall imbrication experienced complete or substantial relief of their preoperative symptoms. However, the symptoms of one patient reappeared eight months after the operation. Another patient experienced a postoperative cerebrospinal fluid leakage. Six of the seven patients treated with the modified surgical operation experienced complete or substantial resolution of their preoperative symptoms, with only one patient who experienced temporary worsening of his preoperative urine incontinence, which disappeared gradually one month later. No new postoperative neurological deficits, no cerebrospinal fluid leaks and no recurrence were observed in the seven patients. The symptoms of the two patients treated with conservative measures aggravated with time. Conclusions Microsurgical operation should be a treatment consideration in patients with symptomatic sacral perineural cysts. Furthermore, the surgical procedure with partial cyst removal and aperture repair for prevention of cerebrospinal fluid leakage seemed to be more simple and effective.